PEMBELAJARAN BAHASA INDONESIA MENUJU MASYARAKAT 5.0 - Hidayati, Eka Suci; Andani, Puput (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstractâ€” Society 5.0 (Sosiety 5.0) is a concept that arises when many people are warmly discussing the discourse of Industry 4.0 with all its implications in various fields, including education. The Community Concept 5.0 first appeared in Japan in 2016 and has since spread and its basic concepts continue to be shaped. Society 5.0 is based on a variety of pillars, including Industry 4.0 and cybernetics or cybernics. Community Vision 5.0 demands transformation in learning. This paper will explain several aspects of Indonesian language learning in the perspective of "Community Era 5.0", especially in terms of student needs, the role of educators, preparation and organization of teaching materials, patterns of mixing in learningKeywordsâ€” student needs, community 5.0, the role of educators, Indonesian language learning, educational transformation.Â Abstrakâ€” Masyarakat 5.0 (Sosiety 5.0) merupakan suatu konsep yang muncul takkala banyak kalangan sedang hangat mendikusikan diskursus Industri 4.0 dengan segala implikasinya dalam berbagai bidang, termasuk bidang pendidikan. Konsep Masyarakat 5.0 pertama kali muncul di Jepang pada 2016 dan sejak itu menyebar dan konsep dasarnya terus dibentuk. Masyarakat 5.0 didasarkan pada berbagai pilar, termasuk Industri 4.0 dan sibernika atau cybernics. Visi Masyarakat 5.0 menuntut adanya trasformasi dalam pembelajaran. Makalah ini akan menjelaskan beberapa aspek pembelajaran bahasa Indonesia dalam perspektif â€œEra Masyarakat 5.0â€, khususnya ditinjau dari kebutuhan siswa, peran pendidik, penyiapan dan pengorganisasi bahan ajar, pola bauran dalam pembelajaran.Kata Kunciâ€” kebutuhan siswa, masyarakat 5.0, peran pendidik, pembelajaran bahasa Indonesia, transformasi pendidikan.Â